2020
DOI: 10.1200/edbk_279881
|View full text |Cite
|
Sign up to set email alerts
|

Current Approaches to the Treatment of Advanced or Metastatic Renal Cell Carcinoma

Abstract: The optimal management approach to advanced or metastatic renal cell cancer of the clear cell type continues to rapidly evolve. Risk stratification of patients into favorable-, intermediate-, and poor-risk categories is now routinely performed. In selected individuals with low-volume indolent disease, active surveillance may be an appropriate option. Cytoreductive nephrectomy and/or surgical metastasectomy may be also be considered for selected patients after evaluation by a multidisciplinary tumor board. Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
32
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 49 publications
0
32
0
5
Order By: Relevance
“…The indication and the role of metastasectomy for patients with metastatic renal cell cancer (RCC) remains unclear. 1 Various retrospective studies have reported the survival benefit resulting from the aggressive complete surgical removal in selected patients. 2 It is also true, however, that there is always selection bias and the results have to be interpreted with caution.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The indication and the role of metastasectomy for patients with metastatic renal cell cancer (RCC) remains unclear. 1 Various retrospective studies have reported the survival benefit resulting from the aggressive complete surgical removal in selected patients. 2 It is also true, however, that there is always selection bias and the results have to be interpreted with caution.…”
mentioning
confidence: 99%
“…1 The European Society for Medical Oncology recommends that patient selection should be discussed within a multidisciplinary team. 1,3 The patients with good performance status, solitary or oligometastases, metachronous disease with disease-free interval >2 years, the absence of progression on systemic therapy, low or intermediate Fuhrman grade, and complete resection may be good candidates and have been associated with favorable outcome after metastasectomy. 1,3 In this issue of IJU Case Reports, Hagimoto et al reported a case of metastatic RCC who achieved a durable response using nivolumab as the fifth-line therapy following the firstline interferon-alpha, the second-line sunitinib, the third-line axitinib, and the fourth-line everolimus.…”
mentioning
confidence: 99%
See 3 more Smart Citations